Nutrient solution atomization and supply device suitable for aerial root plants - WANG XIWEN (2015)
The utility model discloses a nutrient solution atomization and supply device suitable for aerial root plants. The nutrient solution atomization and supply device comprises an atomizer, stand columns, a spray pipe and a feeding pipe. The nutrient solution atomization and supply device is characterized in that beams are arranged between the stand columns, the atomizer is arranged on one beam, and the two sides of the atomizer are provided with a surge chamber and an air blow motor respectively; one end of the spray pipe is connected with the surge chamber, the other end of the spray pipe is provided with a bottom cover, and the spray pipe is provided with spray heads and arranged on the beams; the junctions between the spray pipe and the beams are provided with fastening rings; the feeding pipe is connected with the atomizer and provided with a switch mounting ring, and a switch is arranged on the switch mounting ring. According to the nutrient solution atomization and supply device, the two sides of the atomizer are provided with the surge chamber and the air blow motor respectively, the air blow motor can blow an atomized nutrient solution into the surge chamber, and then the nutrient solution enters the spray pipe, is sprayed out of the spray heads and is evenly spread underneath the aerial root plants to be absorbed by the root systems of the aerial root plants; accordingly, the utilization rate of the nutrient solution is increased, and the nutrient solution atomization and supply device is easy to operate, good in atomization effect and high in working efficiency.